The Impact of Digital Tools on Modern Research Practices: The Role of Institutional Review Boards (IRBs) in Research Ethics - Yekula, Prasanna Kumar; Kobal, Wilson (AG Volumes, 2025)
In the 21st century, the development of digital tool technologies has led to a notable improvement in social science research worldwide. Thanks to these technological advancements, researchers can now easily access and analyse information, manage their time, and create more engaging research. This has completely changed the way that research is conducted. Review of the many studies on the influence of digital technologies on contemporary research methods is provided in this article. It concluded that digital tools, including AI and big data analytics, are transforming modern research practices by enhancing efficiency, data quality, and collaborative capabilities across healthcare, education, and social research. Institutions play a crucial role by investing in infrastructure, training, and ethical frameworks to ensure responsible and effective technology integration. While these tools offer significant advantages, challenges such as data privacy, ethical concerns, and the digital divide must be addressed. By fostering digital literacy, expanding access, and implementing clear guidelines, institutions can harness the full potential of digital tools to advance research practices in an ethical and inclusive manner.